Analisis Keragaman Morfologi dan Biokimia pada Anggrek Phalaenopsis (Orchidaceae) - Handini, Aline Sisi; Sukma, Dewi; Sudarsono, dan (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2016)
ABSTRACTPhalaenopsis orchid is one of famous genera in Orchidaceae family which have high economic value. Phalaenopsis breeding needs to be developed intensively to fulfill market demand for new varieties. The objective of this study was to obtain the information of  morphological and biochemical diversity of a collection of Phalaenopsis orchid which will be useful for Phalaenopsis breeding. Plant materials used were 10 genotypes of Phalaenopsis with various petal colours of white, yellow, pink, deep pink, purple, or combination of yellow and brown. Morphological diversity of 10 genotypes were analyzed based on qualitative and quantitative characters following UPOV guidance for Phalaenopsis, while biochemical diversity was based on pigment content such as chlorophyl, anthocyanin, and carotene in plant roots, leaves and flower petals. The result of this research showed morphological diversity of 10 genotypes used was relatively high, with similarity of 55%. In that level of similarity, genotypes were grouped into two cluster. Biochemical analysis showed that most of genotypes were different for anthocyanin and carotenoid content for each plant organ. Genotype which showed high content of anthocyanin in leaves was Phal. hybrid ‘PH37’ while high content of carotene in leaves was Phal. hybrid ‘PIROUI. High content of anthocyanin in petals were found in Phal. hybrid ‘PH37’ and Phal. esmeralda, and high content of carotene were in Phal. cornucervi and Phal. cornucervi Red. Root with high anthocyanin content was found in Phal. hybrid ‘PIROU1’. There were significant correlation (0.975) for anthocyanin content between leaves and petals, petals and roots (0.953) on Phal.hybrid ‘PH37’, and between leaves and roots (0.874) on Phal. hybrid ‘PIROU1).Keywords: anthocyanin, carotene, chlorophyll, Phalaenopsis, similarity